2012
DOI: 10.3109/17549507.2012.686629
|View full text |Cite
|
Sign up to set email alerts
|

Aphasia treatment: Intensity, dose parameters, and script training

Abstract: Studies of aphasia treatment have shown that intensive speech-language therapy is associated with significant improvements. However, there is no standard definition of intensity and the simplistic notion that “more is better” is not necessarily supported by the research. First, current evidence regarding intensity and aphasia treatment was briefly summarized. Second, studies that directly compare conditions of higher- and lower-intensity treatment for aphasia were reviewed with regard to the inclusion of param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 22 publications
(52 reference statements)
2
61
0
3
Order By: Relevance
“…The problem, however, is that precisely identifying the dosage parameters can be challenging and complicated (Baker, 2012b;Kamhi, 2012). It has obvious application to computer-delivered aphasia treatment wherein the dose and dose form are fairly well prescribed (e.g., Cherney, 2012;Harnish et al, 2014;Off, Griffin, Spencer, & Rogers, 2015). For example, Harnish et al (2014) easily characterized the active ingredients (e.g., semantic, phonemic, and orthographic cues) and dose (50 pictures × 8 cues or presentations = 400 teaching episodes) within their dose form (computer-assisted picture naming).…”
Section: Mixed-model Analysesmentioning
confidence: 99%
“…The problem, however, is that precisely identifying the dosage parameters can be challenging and complicated (Baker, 2012b;Kamhi, 2012). It has obvious application to computer-delivered aphasia treatment wherein the dose and dose form are fairly well prescribed (e.g., Cherney, 2012;Harnish et al, 2014;Off, Griffin, Spencer, & Rogers, 2015). For example, Harnish et al (2014) easily characterized the active ingredients (e.g., semantic, phonemic, and orthographic cues) and dose (50 pictures × 8 cues or presentations = 400 teaching episodes) within their dose form (computer-assisted picture naming).…”
Section: Mixed-model Analysesmentioning
confidence: 99%
“…56,57 Some treatment studies have directly compared conditions of higher and lower intensity treatment for aphasia. 11 Yet, optimal intensity has not been established for even one type of aphasia treatment.…”
Section: Dosagementioning
confidence: 99%
“…With respect to ICAPs in particular, the basic neuroscience literature on intensity and quantity of neurorehabilitation (reviewed in ref. 9) as well as the growing literature on intensity in aphasia treatment 5,[10][11][12] are directly relevant. Theory and basic research are important contributors to Discovery, but we believe that clinical experience can also be informative at this stage.…”
Section: Discovery Phasementioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Almost a decade later, evidence is still equivocal about the efficacy of intensive aphasia therapy and the specific ingredients that allow for the best outcomes for individual persons with aphasia. [38][39][40][41] Cherney et al examined 11studies and found no clear differences in outcomes between intensive and non-intensive treatment protocols. 41 The recommendations from their review were to examine the behavioural and neuroimaging results of intensive treatment independently and in combination with influencing factors.…”
Section: Intensity Of Aphasia Treatmentmentioning
confidence: 99%